2001
DOI: 10.2514/2.5784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fuel Preinjection on Mixing in Mach 1.6 Airflow

Abstract: The effects of injection behind a pylon upstream of a supersonic combustion chamber were evaluated for liquid JP-10 and gaseous ethylene. A generic, rearward-facing, rectangular step was used as the primary ameholding mechanism. A pilot-hydrogen ame injected from the base of the step provided ignition. The fuel was injected from a 1.5-mm-diam wall ori ce behind a thin triangular cross section pylon placed in the isolator at 10 step heights upstream of the step. The role of the pylon is to facilitate the penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The pylons' optimal heights, widths and distances from the injection port are determined from previous computational methods 6 and correlated to sizes used in prior experimentation. 7,8 Designs are determined from the top two configurations which show enhancement of fuel penetration. A schematic of the pylon and injector port design used in this research is given in Figure 1 below.…”
Section: A Test Facility and Hardwarementioning
confidence: 99%
See 1 more Smart Citation
“…The pylons' optimal heights, widths and distances from the injection port are determined from previous computational methods 6 and correlated to sizes used in prior experimentation. 7,8 Designs are determined from the top two configurations which show enhancement of fuel penetration. A schematic of the pylon and injector port design used in this research is given in Figure 1 below.…”
Section: A Test Facility and Hardwarementioning
confidence: 99%
“…Pylon designs were based on the two best geometries determined from a computational study, 6 and correlated with sizes used in separate experimental work. 7,8 The research showed that pylons improved penetration and mixing potential over a baseline transverse injection case without a pylon. However, due to the techniques used, information on aerodynamic losses could not be obtained.…”
Section: Introductionmentioning
confidence: 98%
“…If a flammable mixture of fuel and air resides in the boundary layer, it is possible that combustion could occur well upstream of the combustor, resulting in potentially catastrophic consequences. Results from these studies [11][12][13] suggested that pylon-aided fuel injection could enhance the fuel jet penetration into the supersonic flow, compared with simple wall injection without a pylon. Results also suggested that little, if any, fuel remained in the near-wall region.…”
Section: Nomenclaturementioning
confidence: 99%
“…Pylon-aided fuel injection has been investigated as a method for introducing liquid or gaseous fuel into the supersonic airstream in the inlet duct well upstream of the combustor [11][12][13]. In this approach, a small aerodynamically shaped fin (called a pylon) is positioned just upstream of a fuel injector.…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation